Contemporary developments in Indonesian Islam explaining the "conservative turn" - Bruinessen, Martin van (ISEAS Publishing, 2013)
"There is no doubt that this fine book is a timely anthology on the contemporary developments of Indonesia's post-Suharto Islam and Muslim politics. Edited by Martin van Bruinessen, an eminent Dutch scholar of Indonesian Islam, this collection of essays discusses 'new trends' within Indonesian Islam, namely the rise of Islamic conservatism and religiously-inspired radical-militant Muslim groupings, particularly in the aftermath of the downfall of the Suharto dictatorial regime in May 1998. To provide further evidence -- and convince the ideas -- of the 'conservative turn' in the country's post-New Order Muslim cultures and politics, the book presents in-depth analyses of four case studies, each of which is investigated and written by four Indonesian Muslim scholars" (Pacific Affairs).